2023
DOI: 10.3389/fpsyg.2023.1121986
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation moderates the association between COVID-19 stress and mental distress: findings on buffering, exacerbation, and gender differences in a cross-sectional study from Norway

Abstract: BackgroundMaintaining good mental health is important during a crisis. However, little attention has been given to how people achieve this, or how they evaluate emotions associated with stressors, such as the COVID-19 pandemic. This study aims to (1) investigate whether emotion regulation, in particular cognitive reappraisal and suppression, moderates the relationship between COVID-19 stress and general mental distress and (2) examine gender differences in the interrelations between COVID-19 stress, emotion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 127 publications
4
4
0
Order By: Relevance
“…Ikegami et al [23] found that among a Japanese population-based sample job stress scores were lower among office workers who were allowed to be more frequent telecommuters; paralleling the present findings, their findings further underscore the role of COVID-19 social policies in moderating distress during this period. In particular, the present findings support those of Haver et al [22] that emotional regulation moderated the relationship between COVID-19 stresses and mental distress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ikegami et al [23] found that among a Japanese population-based sample job stress scores were lower among office workers who were allowed to be more frequent telecommuters; paralleling the present findings, their findings further underscore the role of COVID-19 social policies in moderating distress during this period. In particular, the present findings support those of Haver et al [22] that emotional regulation moderated the relationship between COVID-19 stresses and mental distress.…”
Section: Discussionsupporting
confidence: 91%
“…Only a couple studies could be located which examined the effects of moderator variables on the adverse effects of COVID-19 exposure. Haver et al [22] found that cognitive reappraisal buffered COVID-19 stress effects among women and that suppression exacerbated COVID-19 stress effects among men. In a nationwide health survey of Japanese office workers (N = 13.468), after controlling for several demographic factors, Ikegami et al [23] found that job control scores were higher and job stress scores were lower among Japanese office workers who were more frequent telecommuters.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the effect of education on CR and hope-agency might reflect the involvement of cognitive resources in the emotion regulation strategy [ 33 , 34 ] and in hope’s agency component [ 17 ]. The effect of gender on the two emotion regulation strategy scales is in line with previous evidence showing females to more likely rely on CR and males to engage more ES [ 7 , 35 ], even within the COVID-19 pandemic context [ 36 ]. The effect of COVID-19 worries on ES and optimism suggests that such outcomes are likely affected by negative feelings (e.g., worry or fear) possibly arising from the prolonged crises individuals face [ 1 , 3 ].…”
Section: Discussionsupporting
confidence: 85%
“…It was observed that children who use unhealthy emotion regulation strategies like inhibition and dysregulated expression showed a lack of cognitive reappraisal strategy in a time of an emotional crisis ( 61 ). Additionally, these children also showed a low score on the distress tolerance and self-esteem scale, which further signifies the use of a positive emotion regulation strategy to promote a healthy lifestyle and a positive self-image.…”
Section: Discussionmentioning
confidence: 99%